A Step-By-Step Technique for the Piezosurgical Removal of Fractured Implants. Issue 8 (November 2018) - Messina, Antonello Maria; Marini, Luca; Marini, Ettore
Abstract : Abstract: With the increasing popularity of dental implants, the removal of fractured implants has become a major challenge for clinicians. Several tools can be used for the removal of osseointegrated implants; however, few of these have the characteristics of easy control, selective cutting, and rapid healing. In this study, the authors describe a step-by-step technique for the removal of osseointegrated fractured implants via multiple peri-implant osteotomies performed using a piezoelectric device and appropriate inserts. All patients ended with primary wound closure without any soft tissue dehiscence and no healing problems during the postoperative period. As the use of ultrasonic inserts enables precise and selective cuts, piezosurgical implant removal is an attractive alternative to trephine burs or rotary drills.